Human Papillomavirus vaccination coverage among the female population living in the state of Goiás, Brazil, 2014-2020: a time series study - Iana Mundim de Oliveira; Bruno César Teodoro Martins; Leonardo Ribeiro Soares (Ministério da Saúde do Brasil, 2024)
Abstract Objective: To analyze the temporal trend of human papillomavirus (HPV) vaccination coverage among the female population aged 10 to 14 years, living in the state of Goiás, Brazil, between 2014 and 2022. Methods: This was an ecological time series study using data from the Brazilian National Health System Information Technology Department (Departamento de Informática do Sistema Único de Saúde - DATASUS); the annual vaccination coverage rate was calculated based on the number of second doses administered; the trend of the rates was analyzed using the Prais-Winsten model. Results: A total of 407,217 second doses of the quadrivalent HPV vaccine were administered to the female population aged 10-14 years, with annual vaccination coverage rates ranging from 12.3% (2019) to 30.0% (2015), and an annual percentage change (APC) of 0.7% (95%CI 0.9; 0.2; p-value = 0.030). Conclusion: In Góias state, the quadrivalent HPV vaccine coverage rate was below the national target (80%), showing a stationary trend in the time series.